Assessment of hemostasis in dogs with gastric‐dilation‐volvulus, during resuscitation with hydroxyethyl starch (130/0.4) or hypertonic saline (7.5%). Issue 6 (17th October 2021) - Borrelli, Antonio; Giunti, Massimo; Calipa, Stefano; Botto, Angelica; Mengozzi, Giulio; Lisa, Grassato; Maurella, Cristiana; Bruno, Barbara
Abstract: Objective: To compare the impact of an IV bolus of hydroxyethyl starch 130/0.4 (HES) or hypertonic saline 7.5% (HS) on hemostasis in dogs resuscitated for gastric‐dilation‐volvulus (GDV). Design: Open‐label, parallel‐group randomized clinical trial. Animals: Twenty‐three client‐owned dogs. Interventions: Dogs affected by GDV and shock were randomly assigned to receive HES at 10 mL/kg or HS at 4 mL/kg every 15 minutes. Blood samples were collected for blood gas analysis, PCV, total plasma protein, albumin, standard coagulation profile, and thromboelastometry (ROTEM) at baseline (T0) and at the end of bolus (T1). To assess the differences between the 2 groups at T1, Student's t ‐test or Wilcoxon rank‐sum test was used. To evaluate the differences between T0 and T1, ANOVA for paired data or Wilcoxon matched‐pairs signed‐ranks test was used. P  < 0.05 was considered significant. Measurement and main results: Hemostasis was evaluated by means of prothrombin time, activated partial thromboplastin time, fibrinogen, and ROTEM. The study included 13 dogs in the HES group and 10 dogs in the HS group. Differences were found between groups at T1: increase in clotting time ( P  = 0.018) and decrease in fibrinogen level ( P  = 0.021) in the HS‐treated group. Between T0 and T1, there were differences for the HES group: increase in clot formation time ( P  = 0.046), decrease in maximum clot firmness ( P  = 0.002) in ex‐TEM profile, and decrease in maximum clot firmness ( P  = 0.0117) in fib‐TEM profile. Between T0 and T1, the following differences were noted for the HS group: increase in clotting time ( P  = 0.048) and clot formation time ( P  = 0.0019), decrease in maximum clot firmness ( P  = 0.031) and α angle ( P  = 0.036) in ex‐TEM profile, decrease in α angle ( P  = 0.036) in in‐TEM profile, and decrease in maximum clot firmness ( P  = 0.017) in fib‐TEM profile. Conclusion: In dogs affected by GDV, HES or HS infusion caused a similar tendency toward hypocoagulability, with few differences between the 2 groups.